Estudo das Redes de Passes Ofensivas nos Jogos Reduzidos e Condicionados: efeitos induzidos pela manipulação do número e localização das balizas - Conrado Padovam Vieira (2018)
Association football has a complex nature and different domains of knowledge have contributed to understand the factors that improve teams' performance in competition. The social network analysis comprehends a theoretical and practical framework that allows to understand the functional patterns emerging from players' interactions. This methodology considers teams as complex social systems and verifies informational relations (i.e. passes) exchanged between the network agents (i.e. the players). Small Sided and Conditioned Games are considered important task constraints that when correctly utilized and manipulated by coaches during their training sessions allow shaping teams' tactical behaviors. Notwithstanding, there is still a lack of researches on this subject, particularly in which regards the study of social networks. Thus, the aims of this dissertation were to compare the effects of manipulating task constraints (number and location of goals) on teams' passing networks, number of passes and goals, and to ascertain the emergence of prominent players in two different Small Sided and Conditioned Games. A 6 + GK Vs. 6 + GK game was played with a central goal and a 6 vs. 6 game with two-sided mini-goals. A total of 14 athletes (17.9 ± 0.7 years, 175.6 ± 5.7 cm high, 69.7 ± 9.9 kg) were divided into two teams (A and B). The multivariate analysis of variance (ANOVA) was used to measure the density of the social networks, the number of passes and goals scored by teams in both game conditions. A multiple comparison of Bonferroni's test was applied to compare data from both conditions. Results demonstrated statistically significant differences between the means of the density of the social networks and the number of passes between two game conditions. It seems that two-sided mini-goals game can be a possibility for enhancing teams' interactions through ball-passing actions as a training task.